RELEVANCE AND JURISDICTION OF CASES RELATED TO PATERNITY DISPUTES IN UZBEKISTAN (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article is a theoretical and practical analysis of cases related to objections to paternity (maternity) in Uzbekistan, analyzing their relevance and specifics based on national legislation. In addition, the concept of jurisdiction to contest paternity (maternity) and some procedural aspects in the treatment of such cases are discussed.